A quantitative method of approach in designing the mix proportions of fly ash and GGBS-based geopolymer concrete. Issue 1 (2nd January 2018) - Mallikarjuna Rao, G.; Gunneswara Rao, T. D.
Abstract: This paper presents a systematic approach for selecting mix proportions for fly ash and GGBS-based geopolymer concrete. Very little information is available on complete methodology in designing the fly ash and GGBS-based geopolymer mix. The fly ash and GGBS were activated using sodium silicate and sodium hydroxide as alkaline activator solution. The Na2 SiO3 /NaOH (alkaline activator) ratio was taken as 2.5 and the concentration of NaOH solution was maintained at 8 M. The main parameters considered in this study were binder content and alkaline solution/binder ratio for various combinations of fly ash and GGBS. The variables considered in this experimentation include: binder content (360, 420 and 450 kg/m 3 ), proportions of fly ash and GGBS (70–30, 60–40 and 50–50), alkaline solution/binder ratios (0.45, 0.50, 0.55 and 0.60) and curing condition (outdoor curing and oven curing). Results concluded that the GGBS content, alkaline solution/binder ratio and curing condition are found to be most influential parameters on compressive strength and workability of geopolymer concrete. The paper presents detailed examples of mix designs for various strengths.